Association between Prenatal Care Adequacy Indexes and Low Birth Weight Outcome - Vale, Conceição Christina Rigo; Almeida, Nubia Karla de Oliveira; Almeida, Renan Moritz Varnier Rodrigues de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To investigate the association between prenatal care (PNC) adequacy indexes and the low birth weigth (LBW) outcome.Methods A total of 368,093 live term singleton births in the state of Rio de Janeiro (Brazil) from 2015 to 2016 were investigated using data from the Brazilian Live Birth Information System (Sistema de Informações sobre Nascidos Vivos, SINASC, in Portuguese). Seven PNC adequacy indexes were evaluated: four developed by Brazilian authors (Ciari Jr. et al., Coutinho et al., Takeda, and an index developed and used by the Brazilian Ministry of Health – MS) and three by authors from other countries (Kessner et al., the Adequacy of Prenatal Care Utilization index – APNCU, and the Graduated Prenatal Care Utilization Index – GINDEX). Adjusted odds ratios were estimated for the PNC adequacy indexes by means of multivariate logistic regression models using maternal, gestational and newborn characteristics as covariates.Results When the PNC is classified as “inadequate”, the adjusted odds ratios to the LBW outcome increase between 42% and 132%, depending on which adequacy index is evaluated. Younger (15 to 17 years old) and older (35 to 45 years old) mothers, those not married, of black or brown ethnicity, with low schooling (who did not finish Elementary School), primiparous, with preterm births, as well as female newborns had increasing odds for LBW. The models presented areas under the receiver operating characteristic (ROC) curve between 80.4% and 81.0%, and sensitivity and specificity that varied, respectively, between 57.7% and 58.6% and 94.3% and 94.5%.Conclusion Considering all PNC adequacy indexes evaluated, the APNCU had the best discriminatory power and the best ability to predict the LBW outcome.
Keywords: maternal and newborn health; low birth weight; prenatal care; perinatal epidemiology